Pengaruh Bermain Playdough Terhadap Kemampuan Motorik Halus Anak Tunagrahita Sedang Di SLBN A Citeureup Kota Cimahi - Rahmayanti, siti dewi; Permatasari, Resti; Badrujamaludin, Asep; Nurjanah, Nunung; Maharani, Monna (JURNAL KESEHATAN KARTIKA, 2025)
Background: Children with moderate intellectual disabilities exhibit characteristics of stiff and uncoordinated movements, as well as problems in the development of fine motor skills. Fine motor skills in children with moderate intellectual disabilities who are not trained will hinder their fine motor skills. Playdough is a stimulus for improving the fine motor skills of children with moderate intellectual disabilities. Objective: This study aims to determine the effect of playdough on the fine motor skills of children with moderate intellectual disabilities at SLBN A Citeureup, Cimahi City, in 2024. Method: The research design used a pre-experiment with a one-group pretest-posttest approach. The study population consisted of 26 children from grades 1 to 5, selected using purposive sampling. The playdough intervention was conducted four times over two weeks, using an observation sheet for fine motor skills in children with moderate intellectual disabilities as the instrument. Results: The median pretest score was 4.00, while the median posttest score was 7.00, with the lowest score being 0 and the highest score being 9. Bivariate analysis showed a p-value of 0.0001. Conclusion: There is an effect of playdough play on the fine motor skills of children with moderate intellectual disabilities at SLBN A Citeureup, Cimahi City.